Pedagogical and educational aspect of the historical work of M. Arkas “History of Ukraine-Rusʺ - Sharata, N.; Bakumenko, T. (Problems of Engineer-Pedagogical Education, 2023)
Prominent personalities and their historical significance are often represented with regard to their main activity. At the same time, the outstanding personality can be also considered from other point of view; in particular, the activity of M. Arkas, a historian, composer, and the founder of “Prosvita” in the city of Nikolaev, can be analyzed from the standpoint of pedagogical research and achievements. It cannot be argued that it has a great educational and pedagogical potential. Accordingly, we can formulate the purpose of the study, namely: to consider and analyze the work of M. Arkas “History of Ukraine-Rus” in the context of its educational ideal and pedagogical content, focusing on determining the value, place and importance of the ideas of M. Arkas in the context of the cultural and educational movement in Ukraine in the second half of the 19th – early 20th centuries. The methodological basis of the study is grounded on the general scientific principles of historical knowledge and historicity, objectivity, system-orientation, complexity, scientificity, and multifactoriality. Particular emphasis is placed on the use of general scientific methods (biographical analysis, synthesis, and classification), as well as interdisciplinary (structural and systematic approach) and historical (retrospective, problem-chronological, comparative-historical, and descriptive) methods. The scientific novelty of this study is that an attempt was made to expand the pedagogical and educational aspect of the historical work of M. Arkas “History of Ukraine-Rus”. The value of using M. Arkas's creative work as a significant factor in educating patriotic feelings, civic position, and humanity is determined. The researchers are convinced that the key to becoming a true patriot is to study the historical heritage of one’s proper motherland and local people, which served as the basis for writing the book “History of UkraineRus”. M. Arkas brought to the fore the study of the history of the people, which is one of the most valuable spiritual treasures. This is one of the main principles of its educational potential. In addition, there is every reason to consider the book “History of Ukraine-Rus” to be a full-fledged textbook. And it is not just about the popular presentation of material and illustrations; there are such important principles of learning as interest, consistency, and scientific content.